2021
DOI: 10.1111/jnc.15456
|View full text |Cite
|
Sign up to set email alerts
|

Do glia provide the link between low‐grade systemic inflammation and normal cognitive ageing? A 1H magnetic resonance spectroscopy study at 7 tesla

Abstract: Low‐grade systemic inflammation contributes to ageing‐related cognitive decline, possibly by triggering a neuroinflammatory response through glial activation. Using proton magnetic resonance spectroscopy (1H‐MRS) at 7T in normal human individuals from 18 to 79 years in a cross‐sectional study, we previously observed higher regional levels of myo‐inositol (mIns), total creatine (tCr) and total choline (tCho) in older than younger age groups. Moreover, visuo‐spatial working memory (vsWM) correlated negatively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 69 publications
4
18
0
Order By: Relevance
“…Thirdly, we test the hypothesis that higher levels of peripheral inflammation are associated with brain volume loss, and eventually our study's primary endpoint that peripheral inflammation is associated with neurometabolic changes indicating brain inflammation. This investigation elaborates the findings of Lind et al ( 45 ), since we used different peripheral serum biomarkers, added brain GMV measurements, examined more brain regions with 1 H-MRS, and used the MoCA as a more general screening instrument for mild cognitive impairment in older adults. Furthermore, we took into account the effect of age, fat%, and sex and excluded subjects with neurological and psychiatric disorders.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Thirdly, we test the hypothesis that higher levels of peripheral inflammation are associated with brain volume loss, and eventually our study's primary endpoint that peripheral inflammation is associated with neurometabolic changes indicating brain inflammation. This investigation elaborates the findings of Lind et al ( 45 ), since we used different peripheral serum biomarkers, added brain GMV measurements, examined more brain regions with 1 H-MRS, and used the MoCA as a more general screening instrument for mild cognitive impairment in older adults. Furthermore, we took into account the effect of age, fat%, and sex and excluded subjects with neurological and psychiatric disorders.…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, it has been suggested that elevated levels of mIns or mIns/tCr are an early event in the course toward Alzheimer's dementia and can precede tNAA reduction ( 75 ). The previous studies have also reported a positive correlation between pro-inflammatory factors, IL-8 ( 45 ) or CRP ( 76 ) and hippocampal mIns levels after processing the 1 H-MRS data with the LCModel ( 45 ) or in a study where the 1 H-MRS post-processing analytical method was not defined ( 76 ). In our study, we did not find a significant relationship between one of the measured pro-inflammatory factors and mIns levels in the hippocampus with either of the post-processing software packages.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…MRS was performed to assess in vivo markers thought to measure neuroinflammation (Cho, MI and Cr) and neuronal injury (NAA), in cerebral cortex and white matter. 25,26 We hypothesized that ibudilast would decrease peripheral markers of inflammation and increase peripheral markers of anti-inflammation and that participants treated with ibudilast would show lower levels of putative pro-inflammatory neurometabolites and higher levels of antiinflammatory NAA compared to placebo. This study also explored the predictive relationship of neurometabolite markers and subsequent drinking in the trial.…”
Section: Introductionmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy (MRS) allows for the non‐invasive detection of neurometabolites in vivo. Several neurometabolites are thought to serve as markers of neuroinflammation 25,26 . These include myo ‐inositol (MI), a glial marker primarily found in grey matter; choline‐containing compounds (Cho), a marker for cell membrane metabolism and turnover primarily found in white matter; and creatine + phosphocreatine (Cr), a marker for energy reserves of neurons and glia 25 .…”
Section: Introductionmentioning
confidence: 99%